Meningkatkan Kecerdasan Linguistik Anak Melalui Media Gambar Di TK Mawar Jadi Sepakat - Sandina, Faniatri (AL-HANIF: Jurnal Pendidikan Anak dan Parenting, 2021)
This research was conducted because of the low linguistic intelligence of children in Mawar Jadi Sepakat and the inappropriate use of image media. The formulation of the problem studied is how to improve children's linguistic intelligence by using image media at Mawar So Agreed Kindergarten. The purpose of this study is to improve children's linguistic intelligence by using image media. This research is classroom action research. The subject of this research is the Mawar Jadi Sepakat child. The assessment instrument used is observation and data analysis used is qualitative data analysis which can be seen from the predicate category of the success rate of the children's language learning process. The results of the research obtained have increased. Previously, pre-cycle actions were carried out with a percentage of 30%, continued to cycle 1 with a percentage of 45%, cycle 2 75% and in cycle 3 it increased to 85%. After doing research starting from the pre-cycle, cycle 1, cycle 2 and cycle 3, it can be concluded that using animated image media can improve children's language skills in Mawar Jadi Sepakat.